Preservação de jogos eletrônicos: perspectiva transversal de pesquisas e iniciativas - Cruz, Vitória Eduarda Cavalaro (Universidade Federal de São Carlos, 2025)
This research addresses digital preservation with a focus on electronic games. The main objective is to identify initiatives and digital preservation policies related to videogames, linking theoretical discussions in Information Science with practical preservation efforts in Brazil and abroad. The specific objectives are: to define electronic games as informational and cultural objects; to review the literature on digital preservation; to map national scientific production on the subject; and to identify preservation initiatives applied to this medium. This is an applied, exploratory, and qualitative study based on bibliographical and documentary research. Data collection and analysis followed a mapping approach and categorical content analysis. The results indicate that national academic production on the topic is recent and concentrated among a few researchers and institutions. In practice, significant initiatives such as the National Videogame Archive, the Stop Killing Games movement, and Brazil’s Museu do Videogame Itinerante illustrate diverse preservation efforts. The study concludes that although the discussion on digital preservation of videogames is expanding, methodological, legal, and institutional challenges remain to be addressed for the development of sustainable preservation policies in Brazil.
Preservation of electronic games: a cross-cutting perspective on research and initiatives
Keywords: Preservação digital; Jogos eletrônicos; Videogames; Memória digital; Digital preservation; Electronic games; Digital memory; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 9. Indústria, Inovação e Infraestrutura